Pemberdayaan Perempuan Meningkatkan Keterampilan Kegiatan PKK Di Kecamatan Tegal Barat Kota Tega - Tity Kusrina (Cakrawala: Jurnal Pendidikan, 2017)
Women's empowerment of fostering family welfare (PKK) activities through training programs, provision of venture capital, expansion of access to social services, and increased independence. The process of empowerment is directed to vulnerable groups have the capability or empowerment of poverty alleviation and education. The aims of research were identifying and analyzing form factors inhibiting women's empowerment in the organization skills of fostering family welfare (PKK) activities in the District of West Tegal; Analyzing Empowerment of women who developed can give higher yields on skills activities of the fostering family welfare (PKK); Analyzing the support of decision-makers, community leaders and cadres of the fostering family welfare (PKK) as well as for the community, as well as facilities in the organization of society on the skills of women empowerment activities of the fostering family welfare (PKK). The research was qualitative research based on post-positivism, and Data was collected through interviews, observation and documentation. The result of the provision of skills such as making food made from fish, crackers, bananas cake improve skills so that people become motivated to improve the lives of their families. The research suggests that it needs high participation from the members of fostering family welfare (PKK) also the motivation of the board to make the members of fostering family welfare (PKK) become more prosperous.